2022
DOI: 10.3390/tropicalmed7070124
|View full text |Cite
|
Sign up to set email alerts
|

Human-Altered Landscapes and Climate to Predict Human Infectious Disease Hotspots

Abstract: Background: Zoonotic diseases account for more than 70% of emerging infectious diseases (EIDs). Due to their increasing incidence and impact on global health and the economy, the emergence of zoonoses is a major public health challenge. Here, we use a biogeographic approach to predict future hotspots and determine the factors influencing disease emergence. We have focused on the following three viral disease groups of concern: Filoviridae, Coronaviridae, and Henipaviruses. Methods: We modelled presence–absence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…To effectively combat the emergence and spread of disease X and other zoonotic diseases, addressing the underlying drivers that contribute to emergence is crucial [108,109]. Deforestation, wildlife trade, and climate change are key environmental factors that facilitate pathogen spillover from animals-to-humans [110,111].…”
Section: Addressing Underlying Drivers: Tackling Deforestation Wildli...mentioning
confidence: 99%
“…To effectively combat the emergence and spread of disease X and other zoonotic diseases, addressing the underlying drivers that contribute to emergence is crucial [108,109]. Deforestation, wildlife trade, and climate change are key environmental factors that facilitate pathogen spillover from animals-to-humans [110,111].…”
Section: Addressing Underlying Drivers: Tackling Deforestation Wildli...mentioning
confidence: 99%
“…Ever since the first global land cover map was generated through direct observations from remote sensing, such products have increasingly informed global environmental dialogues (34,99). As mapping techniques evolved to incorporate human use of land, populations, and industrial influences across Earth (Figure 3), a myriad of interdisciplinary approaches have allowed scientists to show how human activities can shape biodiversity in a range of ways, including species population declines, invasions, and behavioral changes (72,100,101), facilitating infectious disease spread (102) and compromising crucial ecosystem services, such as water quality and carbon storage and sequestration (83,103). These scientific efforts have been included throughout important environment assessments such as the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services Global Assessments (104), the latest Intergovernmental Panel on Climate Change (IPCC) reports (105), and the Global Biodiversity Outlook (106).…”
Section: How Efforts To Map Human Industrial Transformation Of Earth ...mentioning
confidence: 99%
“…Jagadesh et al employed a biogeographic approach to determine the factors and predict future hotspots for three virus families: the Filoviridae , Coronaviridae , and Henipavirus genera. The study indicated that the common factors influencing disease emergence were climatic variables and human-induced land modifications [ 5 ]. Another study assessed the risk of dengue cases in Indonesia in relation to multi-factorial climate change.…”
mentioning
confidence: 99%